2015
DOI: 10.1371/journal.pone.0135427
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D to PTH(1–84) Ratios Strongly Predict Cardiovascular Death in Heart Failure

Abstract: ObjectivesVitamin D deficiency and hyperparathyroidism are common in patients with heart failure (HF). There is a growing body of evidence supporting the role of vitamin D and parathyroid hormone (PTH) in cardiac remodeling and worsening of HF. Lack of reliable automated testing of 1,25-dihydroxyvitamin D (1,25(OH)2D), the biologically active metabolite of vitamin D, has limited its contribution to the prognostic assessment of HF. Here, the association of 1,25(OH)2D and PTH(1–84) levels was evaluated for predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 57 publications
2
18
0
1
Order By: Relevance
“…After adjusting for multiple confounders, the outcome data from the cohort study are consistent with previous smaller reports in ambulatory patients [9,21,22], hospitalised patients [10] and registry data [3,6,23], and reveal increased mortality in patients with low 25[OH]D concentrations compared with those without. In all of these previous studies, 25[OH]D deficiency was less frequent than in our cohort ranging from 28 to 75% [10,24], whilst overall mortality of the cohorts was higher.…”
Section: Discussionsupporting
confidence: 85%
“…After adjusting for multiple confounders, the outcome data from the cohort study are consistent with previous smaller reports in ambulatory patients [9,21,22], hospitalised patients [10] and registry data [3,6,23], and reveal increased mortality in patients with low 25[OH]D concentrations compared with those without. In all of these previous studies, 25[OH]D deficiency was less frequent than in our cohort ranging from 28 to 75% [10,24], whilst overall mortality of the cohorts was higher.…”
Section: Discussionsupporting
confidence: 85%
“…Improvement in clinical symptoms after vitamin D and calcium supplementation for the treatment of hypovitaminosis and hypocalcemia signifies the importance and protective role of vitamin D in cardiomyopathy [9–10, 3439] (Table 1). Gruson et al [40] suggested that serum 1,25(OH) 2 D 3 and its ratio to parathyroid hormone (PTH) (1–84) strongly and independently predict cardiovascular mortality in chronic HF. Additionally, Leon Rodriguez et al [41] suggested that vitamin D receptor (VDR) polymorphisms may also be a risk factor for increased susceptibility for cardiomyopathy and reported the increased probability of cardiac complications such as chronic Chagas cardiomyopathy with rs2228570*A VDR allele due to impaired immune response against T. cruzi .…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…Our data demonstrate that end-stage heart failure patients have very high FGF-23 values and very low 1,25(OH) 2 D levels before and after LVAD implantation. We [9,11] and others [8,10,12] have already reported that elevated FGF-23 levels and low 1,25(OH) 2 D levels are both independently associated with poor clinical outcome in HF patients.…”
Section: Discussionmentioning
confidence: 99%